Speeding up fermionic lattice calculations with photonic accelerated inverters - Attanasio, Felipe; Bauer, Marc; Dijkstra, Jelle; Lee, Timoteo; Pawlowski, Jan M.; Pernice, Wolfram; Brückerhoff-Plückelmann, Frank (Computer physics communications, 2025)
Lattice field theory (LFT) is the standard non-perturbative method to perform numerical calculations of quantum field theory. However, the typical bottleneck of fermionic lattice calculations is the inversion of the Dirac matrix. This inversion is solved by iterative methods, like the conjugate gradient algorithm, where matrix-vector multiplications (MVMs) are the main operation. Photonic integrated circuits excel in performing quick and energy-efficient MVMs, but at the same time, they are known to have low accuracy. This can be overcome by using mixed precision methods. In this paper, we explore the idea of using photonic technology to fulfil the demand for computational power of fermionic lattice calculations. These methods have the potential to reduce computation costs by one order of magnitude. Because of the hybrid nature of these methods, we call these ‘photonic accelerated inverters (PAIs)’.
Gesehen am 22.01.2026